Tissue Distribution of Factor VIII Gene Expression In Vivo – A Closer Look - Hollestelle, Martine J.; Thinnes, Terri; Crain, Karen; Stiko, Ann; Kruijt, Johan K.; van Berkel, Theo J.C.; Loskutoff, David J.; van Mourik, Jan A. (Thrombosis and Haemostasis, 2001)
Previous studies have shown that factor VIII (FVIII) is expressed by multiple tissues. However, little is known about its cellular origin or its level of expression in different organs. In the present study, we examined FVIII gene expression in different tissues on a quantitative basis. Most of the tissues, especially liver and kidney, expressed high levels of FVIII mRNA compared to their level of expression of other hemostatic proteins, including von Willebrand factor (VWF). This was unexpected since FVIII is a trace protein. In situ hybridization analysis confirmed that liver and kidney were rich in FVIII mRNA. In the liver, a clear hybridization signal was detected in cells lining the sinusoids. FVIII mRNA analysis of purified liver cells confirmed the expression of FVIII mRNA by sinusoidal endothelial cells and Kupffer cells. Low but significant levels of FVIII mRNA were also detected in the hepatocytes. VWF mRNA was not detectable in these cells. Similarly, immunohistochemical staining of liver tissue revealed that FVIII protein is primarily associated with sinusoidal cells. VWF protein was predominantly located in the endothelium of larger vessels. In the kidney, FVIII synthesis was localized to the glomeruli and to tubular epithelial cells. Taken together, these results suggest that besides hepatocytes, non-parenchymal cells (e.g. sinusoidal endothelial cells) contribute to FVIII synthesis. VWF synthesis is primarily confined to extra-hepatic tissues.
Keywords: Factor VIII; biosynthesis; von Willebrand factor; endothelial cell